An efficient method for image archiving: Tagging images with structered keywords - SAÇAK, BÜLENT (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Photographic documentation is an integral part of plastic surgery practice. While there are reports in the literature that discuss photographic documentation and archive security, it is hard to find studies on image archiving and searching. This report aims to introduce a structured tagging system that can be used with all digital archiving programs and easily adapted to the everyday routine and practices of users. The system facilitates finding the images of a patient that were photographed at different times and allows to quickly and easily view all images related to a certain anatomical region or all of those that were photographed with a certain technique.
Keywords: Archiving; photography; tagging